2012
DOI: 10.1021/es302157j
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Selectivity in Natural Organic Matter Studied with Nitroxyl Paramagnetic Relaxation Probes

Abstract: Sorption site selectivity and mechanism in natural organic matter (NOM) were addressed spectroscopically by the sorption of paramagnetic nitroxyl compounds (spin probes) of different polarity, TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) and HTEMPO (4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl). The sorbents were Pahokee peat, Beulah-Zap lignite, and a polystyrene-poly(vinyl methyl ether) (PS-PVME) polymer blend representing the mixed aliphatic-aromatic, polar-nonpolar character of NOM. Nuclear-electron spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
(94 reference statements)
4
20
0
Order By: Relevance
“…Kwon and Pignatello (2005) showed that glass beads (1.7 g) coated with vegetable oil at the level of 5 or 14 wt % did not show increased CO 2 uptake compared with glass beads alone, thereby giving no evidence of CO 2 dissolution. Lattao et al (2012) examined a 1:1 polymer blend of polystyrene and polyvinyl methyl ether, which contains both nonpolar aromatic and polar aliphatic groups and forms a homogeneous rubbery film when cast from toluene. That material sorbed little CO 2 (8.2 μL g −1 OC) and showed negligible microporosity.…”
Section: Resultsmentioning
confidence: 99%
“…Kwon and Pignatello (2005) showed that glass beads (1.7 g) coated with vegetable oil at the level of 5 or 14 wt % did not show increased CO 2 uptake compared with glass beads alone, thereby giving no evidence of CO 2 dissolution. Lattao et al (2012) examined a 1:1 polymer blend of polystyrene and polyvinyl methyl ether, which contains both nonpolar aromatic and polar aliphatic groups and forms a homogeneous rubbery film when cast from toluene. That material sorbed little CO 2 (8.2 μL g −1 OC) and showed negligible microporosity.…”
Section: Resultsmentioning
confidence: 99%
“…It allows us to observe, understand, and investigate the nature and molecular mechanisms of complex processes in soils, including the formation of non-extractable residue upon interaction between aromatic amines of organic xenobiotics and soil [20][21][22][23][24]. Understanding the molecular mechanisms of soil's response to external stress conditions, including contamination, will contribute not only to our basic knowledge of the soil, its structure, and functions, but also to the development of methods for reducing the impact of stress on soil, soil remediation, and rational land use.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, amines are contained in pesticides, biocides, and veterinary pharmaceuticals that enter the soil due to human economic activities. Many authors have shown that these contaminants are strongly bound to soil constituents with the partial formation of polymer structures, but the mechanisms of binding are still not understood [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[94] In particular, solid-state 13 C-NMR spectra of NOM were used to identify a specific molecular region in which T 1ρ H, T 1 H, and T 1 C relaxation times were selectively reduced as a function of the proximity of fluctuating magnetic fields produced by the unpaired electrons of probes. They found that the paramagnetic effect was distributed along all functional intervals of NOM spectra and no selective interactions were observed, thereby failing to reveal any preferential sorption on specific molecular structures of NOM.…”
Section: Relaxation Timesmentioning
confidence: 99%
“…They found that the paramagnetic effect was distributed along all functional intervals of NOM spectra and no selective interactions were observed, thereby failing to reveal any preferential sorption on specific molecular structures of NOM. [94] In binding studies between small ligands and large sorbents, signals of the large molecule frequently overlap those of the ligand, thus preventing a clear detection of the latter. This problem is successfully overcome by applying pulse sequences, which introduce different NMR filters and enable simplification of mixture spectra by selectively attenuating the undesired signals.…”
Section: Relaxation Timesmentioning
confidence: 99%